Media Framing Analysis in National News Regarding the Issue of Sending Suspected LGBT Students to Military Barracks - Ghina Reftantia; Randy William; Ariendra Jamine Prameswari; Diana Dewi Sartika; Erlisa Saraswati; Yuanita Dwi Hapsari (Saree: Research in Gender Studies, 2026)
This study examines the construction of reality in the online media coverage by Detik.com and Tribunnews.com, from May 2 to 8, 2025 (coverage news period). The coverage focuses on the Regent of Cianjur Regency’s decision to send students alleged to be LGBT to military barracks. Using a qualitative approach and Robert N. Entman's framing analysis method within the constructivist paradigm, this study focuses on four components of framing analysis: problem definition, causal interpretation, moral evaluation, and treatment recommendation. Data were derived in the form of four news stories (two news articles from each media) and were selected purposively to allow for an in-depth analysis of the framing strategies used. The results show that both media frame the issue from different perspectives. The findings suggest that Detik.com constructs its coverage through an informative frame shaped by nationalist ideology and an orientation toward objectivity, while Tribunnews.com frames its reporting by foregrounding moral judgements and controversial aspects. These findings demonstrate that the media not only convey facts but also reconstruct reality according to their respective ideologies and news orientations. This research is significant because the LGBT issue remains a social and political debate in Indonesia, so media framing has been influenced and shaped public opinion, moral perceptions, and the direction of government policy. Thus, by understanding how the media frames this sensitive issue, readers and researchers can be more critical in interpreting information and its impact on the construction of social reality Abstract Indonesian: Penelitian ini menganalisis konstruksi realitas dalam liputan media daring Detik.com dan Tribunnews.com terkait isu pengiriman mahasiswa diduga LGBT ke barak militer oleh Bupati Cianjur dalam kurun waktu 2-8 Mei 2025. Dengan menggunakan pendekatan kualitatif dan metode analisis framing model Robert N. Entman dalam paradigma konstruktivis, penelitian ini berfokus pada empat komponen analisis framing: definisi masalah, interpretasi kausal, evaluasi moral, dan rekomendasi penanganan. Data berupa empat berita (dua artikel berita dari setiap media) dipilih secara purposif untuk memungkinkan analisis mendalam terhadap strategi framing yang digunakan. Hasil penelitian menunjukkan bahwa kedua media membingkai isu dari perspektif yang berbeda. Detik.com cenderung menampilkan frame informatif dengan ideologi nasionalis yang menekankan objektivitas, sementara Tribunnews.com menekankan aspek moralitas dan kontroversi. Temuan ini menunjukkan bahwa media tidak hanya menyampaikan fakta, tetapi juga merekonstruksi realitas sesuai dengan ideologi dan orientasi beritanya masing-masing. Penelitian ini penting karena isu LGBT masih menjadi perdebatan sosial dan politik di Indonesia, sehingga pembingkaian media berpotensi memengaruhi opini publik, persepsi moral, dan arah kebijakan pemerintah. Oleh karena itu, dengan memahami bagaimana media membingkai isu-isu sensitif ini, pembaca dan peneliti dapat lebih kritis dalam menafsirkan informasi dan dampaknya terhadap konstruksi realitas sosial.